Odpowiedzi

2009-12-13T22:40:58+01:00
2√3+5 | *3√2 (2pierwiastki z 3+5)*3√2 6pierwiastków z 6+15√2
--------- = ------------------------------- = ----------------------------=
3√2 |*3√2 18 18

= pierwiastek z 6+15√2
--------------------------
3
Najlepsza Odpowiedź!
2009-12-13T22:40:48+01:00
2√3+5
--------=
3√2

Mnozysz przez podstawe :)

2√3 × 3√2 + 15√2
---------------------=
3√2×3√2

6√6+ 15√2
------------=
18

i teraz mozesz skrocic to :)

2√6 + 5√2
------------
6
  • Użytkownik Zadane
2009-12-13T22:42:17+01:00
(2√3+5) x 3√2
---------------------
3√2 x 3√2



6√6 +15√2
------------
18